An adaptive architecture for strategic Enhancement of energy yield in shading sensitive Building-Applied Photovoltaic systems under Real-Time environments - Ranjan Satpathy P.; Ramachandaramurthy V.K.; Roslan M.F.; Motahhir S. (Elsevier Ltd, 2025)
Building Applied Photovoltaic (BAPV) systems play a crucial role in developing renewable energy-generating architecture, particularly in urban settings. The BAPV arrays are designed considering the roof area and other installation factors to meet the building's energy demand or contribute to the grid. However, the BAPV array encounters a significant challenge of partial shading by nearby trees or buildings that substantially reduce the generation efficiency. This paper proposes an energy yield enhancement solution for the BAPV system, focusing on the electrical reconfiguration of the arrays during partial shading. The solution, which employs a streamlined architecture with lower switches integrated with the dingo algorithm, ensures fast and reliable operation during dynamic shading scenarios. The solution's efficiency is demonstrated in simulation using a BAPV system, considering real-time partial shading caused by neighbouring objects at different times of the day, considering the sun's movement, and comparing it with existing techniques. The results show that the solution can yield 28.79 % and 15.53 % higher power than the conventional and existing techniques, with an average convergence rate and voltage standard deviation of 0.057 s and 1.26 %, respectively, thereby proving its superiority. ? 2024 Elsevier B.V.